As contribuições do PIBID no processo de formação de professores de ciências - Oliveira, Aline Alves de (2015)
The PIBID (Programa de Bolsa de Iniciação à Docência, in English "Initial Docency Scholarship Program") has gaining more and more importance, since its implementation in higher education institutions, by Capes in 2007, seeking to encourage and value the teacher's initial shaping and improve the quality of basic education. This research wants to investigate the contributions and the program meanings to MEC (Ministério da educação, in English, "Education Ministry"), to UEM (State University of Maringá), and to science itself. The research presents qualitative approach and the information sources were PIBID documents, such as MEC/CAPES/FNDE Notices, the institutional PIBID plan at UEM, the UEM science subproject, and interviews with science graduates. For the interview analysis we used the content analysis. It was possible to understand and reflect on the program importance to reframe the science teacher's initial shaping. Among the findings reached, it was possible to identify that PIBID is understood, by MEC and UEM as a way to enhance the teaching profession, especially in the initial shaping, through scholarships for undergraduate students since the beginning of its graduation, in order to develop projects related to their decency initiation, and by this way, ensure the delivery of demanded teachers in basic education; as improvements in the initial shaping, through discussions and development of new ideas and methodological approaches, that are considered innovative by the researchers in the science teaching area; by the reflection under the social function of the school about the teacher role in an specific school context and through the recognizing of the school as a field of experiences for the initial teacher's shaping.